ANALISIS LELANG EKSEKUSI YANG DILAKUKAN KANTOR PELAYANAN PAJAK PRATAMA SIBOLGA TERHADAP LELANG EKSEKUSI PAJAK NOMOR : PENG-01/WPJ.26/KP.06/2020 (STUDI : KANTOR PELAYANAN PAJAK PRATAMA SIBOLGA) - Avissa Novali Noor (Jurnal Abdi Ilmu, 2021)
The problem in this research is how relevant the role of Taxation Law and its Relation to Auctions; what is the tax collection procedure until the tax execution auction is carried out by the Sibolga Pratama Tax Service Office, and what is the law on the tax object being auctioned with the auction number: PENG-01/WPJ.26/KP.06/2020 by the Sibolga Pratama Tax Service Office because there are no interested parties or bidders for an auction that has been held 4 (four) times, and has entered the billing expiration date? This type of research is a normative juridical research, with descriptive analysis research nature sourced from primary data sources and secondary data collection is carried out by literature studies and field studies by conducting interviews, and data analysis carried out is qualitative data analysis. Based on the results of the research, the role of auction in tax law is very useful where auction is an effort in the tax collection process, which contributes to revenue. The existence of regulations regarding tax collection (Law No. 19 of 2000) and Standard Operating Procedures (SOP) makes the billing procedure at KPP Pratma Sibolga the same as other KPPs, only the proportion and realization of the constraints are different. And efforts to publish the announcement of the auction of PENG-01/WPJ.26/KP .06/2020 which have expired, in the absence of rules regarding the limit of re-auction for confiscated objects, make the confiscated objects have no law. The legal principle of Litis Finiri Oportet states that every case must have an end in order to provide legal certainty. and when the expiration date is determined, there is a legal principle which states that if the main case is lost, the assessor's case or the case he is traveling with in this case involves ending all collection efforts or returning to the decision determined by the DGT.